Wyzwania dla mediów społecznościowych w kontekście rosyjskiej dezinoformacji - Pawlak, Piotr (Studia Europaea Gnesnensia, 2024)
In recent years, the European Union has adopted a number of active measures to prevent, combat and mitigate the effects of Russian disinformation. This effort relies primarily on the legislation which regulates how the media in Europe operate, with particular emphasis on large online platforms. This is due to the fact that social media are a major domain where Russian propaganda is disseminated, thus posing a threat to the election processes in democratic states. In order to safeguard such processes, the EU developed a legal framework which is discussed and reflected on in this study.